Internal auditing's role in preventing and detecting fraud: An empirical analysis - Annika Bonrath; Marc Eulerich (International Journal of Auditing, 2024)
Internal auditing plays a pivotal role in preventing and detecting fraudulent activities. However, the orientation and role of internal auditing in dealing with fraud risk can vary significantly across different companies. This study examines the relationship between the internal audit function (IAF) and fraud, providing new insights into the current practices of internal auditing. Using a survey dataset comprising responses from 275 Chief Audit Executives across Germany, Switzerland and Austria, we investigate factors that correlate with an increased propensity for IAFs to engage in fraud prevention and detection. Our findings suggest that a robust corporate governance environment significantly influences the extent to which the IAF is involved in preventing and detecting fraud. Shedding light on the positioning of internal auditing between management and the audit committee with respect to fraud, our results show that increased IAF involvement with management positively affects the level of activities to prevent and detect fraud, while increased IAF involvement with the audit committee has the opposite effect. Furthermore, we find that the propensity of IAFs to engage in fraud prevention and detection increases when the IAF applies technology-based auditing techniques for risk identification. Our results have implications for building appropriate protection against the steadily increasing risk of fraud within organizations, while holistically addressing the ambiguity regarding the responsibility for preventing and detecting fraud.
Keywords: 650; corporate governance; fraud; internal auditing